ANALISIS KEPUASAN PELANGGAN KENDARAAN TOYOTA TIPE AVANZA PADA PT HASJRAT ABADI CABANG TENDEAN - Christian Wungkar; Nancy Nancy (MANAJEMEN ADMINISTRASI BISNIS DAN PEMASARAN, 2022)
Service is important in achieving company goals, companies that are able to provide thebest service will foster customer satisfaction with the performance of the servicesprovided and can increase sales. This study aims to determine customer satisfaction ofToyota Avanza type vehicles at PT Hasirat Abadi Tendean branch and to determinecustomer satisfaction implementation of Toyota Avanza type vehicles that should be usedat PT Hasirat Abadi Tendean branch. This type of research is quantitative research withdescriptive method. The sample used is a purposive sampling. Analysis of the data usedis the percentage. Based on the results of this study, it can be concluded that there areindicators that need to be improved and indicators that need to be improved, indicatorsthat need to be improved include keeping promises with customers and punctuality in anagreement with customers. The company must improve employee performance, especiallyin indicators of employees keeping promises in an agreement. and employees providepunctuality at the time of the agreement with the way the company needs to conductsocialization, guidance or job training on how to serve customers well